The effect of 2 weeks tapering period on plasma cortisol, GH and performance in female swimmers - مونا رضایی; مسلم بای; سمیه نامدار طجری (Shahid Beheshti University, 2013)
Purpose: The purpose of this study was to compaire the different training stress on fasting concentrations on plasma cortisol, GH and performance in female swimmers. Method: Thirty female swimmers underwent a 12-weeks period of heavy training in and out of the water and then, divided into two equally control (n=15) and experimental (n=15) groups. Control group continued their past training but the experimental underwent a 2-weeks taper period with same intensity and reduced volume and frequency. The fasting blood samples were obtained to measuring hormones before and after the heavy training period and after the following tapering period. The 50 & 100 m performance of all subjects were measured in each section. The Independent-Samples T Test and Paired-Samples T test were used to analyze data (P<0.05). Findings: The findings showed that the mean of samples cortisol decreased because of 2 weeks tapering. And on the other hand we had a fewer increase in the mean of GH. Similarly, swimming performance was significantly improved (P>0.05). Conclusion: In general, we concluded that a good tapering period can be suggested to improve athlete's performance.